The Problem of Practice Dissertation: Matching Program Goals, Practices, and Outcomes - Belzer, Alisa; Axelrod, Tali; Benedict, Cathleen; Jakubik, Tara; Rosen, Michelle; Yavuz, Olcay (The EdD and the Scholarly Practitioner(HC), 2016)
The purpose of this book is to highlight the efforts of the members of the Carnegie Project on the Education Doctorate (CPED) to prepare Scholarly Practitioners in the field of education leadership. The volume is edited by Jill Alexa Perry, Executive Director of CPED, a consortium of 86 schools of education in the US, Canada and New Zealand. CPED is a collaboration of faculty working together since 2007 to re‐envision professional practice preparation in education. Contributing authors include faculty and graduates from CPED‐influenced programs. Faculty members highlight the need to rethink and strengthen all aspects of doctoral level preparation for practitioners, the expanded and enhanced role of research, inquiry and the dissertation in practice, and discuss the implications these changes have on university schools of education. Students and graduates, who face pressing educational issues in their daily lives, reflect on the impact their EdD program has had on their professional practice.
Keywords: dept.edl

On Becoming a Leader - Gregory, J.L. (Educational Leadership: Perspectives on Preparation and Practice, 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedag...
Keywords: dept.edl

Diversity & Cultural Competence - Labas, G; Gregory, J.L. (Educational Leadership: Perspectives on Preparation and Practice, 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedag...
Keywords: dept.edl

Research and Program Evaluation - Haynes, N.M.; Gregory, J.L.; Diffley, W.J. (Educational Leadership: Perspectives on Preparation and Practice, 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedag...
Keywords: dept.edl

Behavior Management: Traditional and Expanded Approaches - Haynes, Norris M. (UPA, 2012)
Keywords: dept.eco

Group Dynamics: Basics and Pragmatics for Practitioners - Haynes, Norris M. (University Press of America, 2012)
Keywords: Social groups; Group facilitation; dept.csp; dept.eco; faculty_collection

Sabbatical leave report. - Gregory, Jess L. (2019)
Sabbatical to write textbook: "School leadership for learning : learning theory to improve professional practice".
Keywords: dept.edl; faculty_collection; sabbatical_report

Mobile Learning: Perspectives on Practice and Policy - Herro, Danielle; Arafeh, Sousan; Ling, Richard Seyler; Holden, Chris (Digital media and learning, 2018)
Keywords: Mobile communication systems in education; United States; United States; Internet in education; dept.edl; faculty_collection

Constructing Your Dissertation: A Guide for Students as They Begin Their Doctoral Research - Gregory, Jess L. (CreateSpace, 2016)
Keywords: Authorship; Academic writing; Dissertations, Academic; dept.edl; faculty_collection

Educational Leadership: Perspectives on Preparation and Practice - Haynes, Norris M.; Arafeh, Sousan; Magagula, Cynthia McDaniels (University Press of America, ® Inc., 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedagogical and experiential learning models as well as provocative new paradigms of their own to help prepare leaders and reinforce leadership effectiveness.
Keywords: Educational leadership; School management and organization; dept.edl; faculty_collection

Comparative Perspectives on International School Leadership: Policy, Preparation, and Practice - Magno, Cathryn S. (Routledge, 2013)
Through a multi-country study, Comparative Perspectives on International School Leadership examines the current global spread of educational leadership, occurring rapidly and widely. Exploring five international case studies of leadership policy, preparation, and practice under the framework of policy borrowing and adaptation, Magno attempts to understand and account for commonalities and differences across country contexts. Rather than assuming a particular model or theory to leadership is best, Comparative Perspectives on International School Leadership takes a policy-orient
Keywords: Cross-cultural studies; Cross-cultural studies; School management and organization; Educational leadership; dept.edl; faculty_collection

Building bridges of empowerment to improve students' achievement: A dicussion of alternative models - Hayford, B.K. (Multiculturalism in the Age of the Mosaic: Essays in Honor of Rudolph G. Wilson, 2010)
Keywords: dept.edl

Improving access and equity in tertiary education in Ghana: The role of private tertiary educational institutions - Hayford, B.K. (Multiculturalism in the Age of the Mosaic: Essays in Honor of Rudolph G. Wilson, 2010)
Keywords: dept.edl

Assessment research - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Keywords: dept.edl

Commonalities And Differences Of District Stories Of Using Curriculum To Improve Achievement - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Keywords: dept.edl

Curriculum: District stories of a path to improved achievement - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
A curriculum is not known to improve academic achievements. This book offers case studies of three Connecticut districts of high, medium and low socio-economic status, three districts from a national sample that won the prestigious Booker prize mainly representing low SES districts, and 10 districts that have implemented a Balanced Curriculum with a sample of various SES districts from high to low. All of them have used their curriculum as the vehicle toward improved achievements. The districts studied have four common themes, represented by the acronym "ASIA", for Alignment, Structure and Stability, Implementation and Infrastructure, and Assessment. All districts aligned their curriculum to state standards and assessments. They had a structure for the curriculum and had stability at the superintendent's position. The districts applied a lot of effort and attained results from implementing the curriculum and developing the infrastructure to support implementation, and they finally incorporated frequent district-wide assessments into their design. The book documents the subsets of these four areas that were present in most districts that might help other districts to replicate the findings. Research in the four areas is also documented. This book demonstrates through the case studies that it is possible to use curriculum as a framework for raising test scores. This is not normally thought of as a path to improved achievements. The fact that districts from a wide range of socio-economic statuses have used their curriculum to improve achievements demonstrates that a wider application of this direction could yield positive results for other districts. © 2014 by Nova Science Publishers, Inc. All rights reserved.
Keywords: dept.edl

Curriculum structure and district leadership stability - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Keywords: dept.edl

Implementation: A model for making implementation plans - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Keywords: dept.edl

Other Popular Avenues For District Improvement: Using Asia To Assess Their Power - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
In reading through the district stories about using curriculum as a framework for improvement, many innovations were interwoven into ancillary efforts for curriculum development. As these are part of the stories of district curriculum development, we thought that discussions of these "ancillary efforts" were important. The innovations considered in this chapter are: Power standards, Professional learning communities, Common assessments, Data-driven decision making, and Walk-through's. We will consider these as if they were being implemented alone, and assess their power to produce student achievement gains using the ASIA framework. References to the district stories will be given. © 2014 by Nova Science Publishers, Inc. All rights reserved.
Keywords: dept.edl

Planning Curriculum Development and Implementation - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Working with districts over the past 15 years to write and implement a balanced curriculum has been a wonderful experience; especially as so many of the districts that I worked with saw their student achievement improve (Squires, 2013). Now, thousands of students are getting better results because the curriculum was developed and well implemented using the Balanced Curriculum model. As is evident by the chapters about other school districts, the balanced curriculum is not the only way to get improvement, as the districts highlighted in this book also used curriculum as a framework for improving achievement. In this chapter I will highlight lessons learned along the way about developing and implementing curriculum. Using ideas described in chapter 6, we will highlight what major roles need to know and be able to do in planning, developing and implementing curriculum. For those with experience of working within a district, this will give one model to compare your district's curriculum writing and implementation efforts. We begin by dividing the effort into three areas: planning, writing, and implementing curriculum. To plan, we create a planning team to guide the process of writing and implementing curriculum. We don't separate curriculum writing from curriculum implementation because how the curriculum is implemented will, in part, depend on how the curriculum was written. We believe that such curriculum development and implementation has the potential to last over several years, and we believe that such an effort needs people who can stay the course over those years, so the effort is not wasted. © 2014 by Nova Science Publishers, Inc. All rights reserved.
Keywords: dept.edl

The alignment research - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Keywords: dept.edl

The balanced curriculum model - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Keywords: dept.edl

Super teachers - Corde, Salvatore J. (Phi Delta Kappan, 2012)
Superintendents have the responsibility to engage in the act of teaching their colleagues what they have learned about the most important work of school districts-ensuring high student achievement. They also must provide strong leadership that will foster and nurture powerful learning communities.
Keywords: dept.edl

Exploring the impacts of school reforms on underrepresented urban students’ college persistence - Yavuz, Olcay (Educational Research and Evaluation, 2016)
This longitudinal quantitative study investigates how participation in the Comprehensive College Readiness Access and Success Program (CCRASP) affects underrepresented urban students’ college persistence. Results revealed that CCRASP participation was associated with higher percentages of students enrolling in both 2- and 4-year colleges as sophomore students. As school leaders and policy makers seek to make all urban students college and career ready, these findings further solidify current urgencies to re-visit K–12 student academic and counselling services. It also provides school leaders and educators with practical information and reform ideas to improve underprivileged students’ persistence and success. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Research-supported school reforms; at-risk students; college persistence; dept.edl; programme evaluation

Curriculum mapping in higher education: a case study and proposed content scope and sequence mapping tool - Arafeh, Sousan (Journal of Further and Higher Education, 2016)
Best practice in curriculum development and implementation requires that discipline-based standards or requirements embody both curricular and programme scopes and sequences. Ensuring these are present and aligned in course/programme content, activities and assessments to support student success requires formalised and systematised review and development processes. These processes are not always in play in higher education, however. Using a descriptive qualitative case study strategy, this article shares how policy outcomes within intermediate and superintendent certification, sixth-year and Ed.D. doctoral courses and programmes at a state university were reviewed, mapped and assessed using an evidence-based curriculum analysis model and tool that mapped standards and outcomes from course syllabus data. Strengths and weaknesses of this approach are discussed and it is suggested that the field might benefit from a curriculum mapping and analysis method that also considers content coverage. A Course-Level Content Scope and Sequence Mapping Tool, developed to map content scope and sequence alongside standards or outcomes mapping, is presented for consideration and testing. The ability to assess and improve curriculum is only as good as the conceptual frameworks, methods and tools available. This critical case study is one effort to advance the field by drawing attention to the importance of curricular content mapping. The study should be of interest to higher education staff, researchers and accreditors concerned with postsecondary programmes and their curricular scope and sequence coherence, quality and improvement. © 2015 UCU.
Keywords: Curriculum; content; content mapping; curricular content; curricular scope and sequence; curriculum mapping; curriculum mapping tool; dept.edl; educational leadership; higher education; policy; programme coherence

Provoking perspectives of creativity and innovation in leadership: innovation, accountability, and the human side of change - Gregory, Jess L (Journal of Leadership Studies, 2016)
Keywords: dept.edl; peer-reviewed

Building Social Capital from the Inside Out: Leveraging Intrapower (Personal Capital) - Haynes, Norris M. (Social Capital and Community Well-Being : The Serve Here Initiative, 2016)
In this writer’s view, the building of social capital starts with the development of personal individual capital. The author posits that an individual may not be optimally effective in building meaningful social relationships and networks, or in influencing results in one’s community that serve the individual and others well, unless the individual has the prerequisite personal attributes and skillsets to do so. Therefore, in this chapter, the author identifies four key personal capital attributes that he sees as foundational to the building of social capital from the inside out. The dynamic synergistic interface among these four core attributes (Control, Empathy, Awareness, and Resolve), is referred to in this chapter as “Intrapower that is seen as a potent facilitative force in the effective building of social capital.
Keywords: Achievement motivation; Civic engagement; Mindfulness; Resilience; Self-awareness; Self-control; Self-regulation; Social & emotional; Youth development; dept.edl

The balanced curriculum model: Description and results - Squires, David (SAGE Open, 2013)
The Balanced Curriculum is a web-based tool that school districts use to create, align, assess, and manage their curriculum development and implementation. The courses are divided into time-bound units with significant tasks (or assured activities) that local district teachers develop and promise to teach. The significant tasks are aligned to standards and assessment specifications. District curriculum authors also develop assessments for all to use when implementing the curriculum. Results of more than 15 years of implementation show that all districts that have developed curriculum using this model, and ensured implementation, have had significant improvement on their test scores. Implications for teachers, principals, and central office staff are given at the end of the article. © The Author(s) 2013.
Keywords: Curriculum; Student achievement results; dept.edl

Culturally responsive leadership: best practice in integrating immigrant students - Magno, Cathyrn S; Schiff, Margo (Intercultural Education, 2010)
Keywords: dept.edl

A quantitative exploration of students’ mindsets and behaviors: A whole child academic, emotional, and career development - Yavuz, Olcay (International Journal of Educational Reform, 2019)
The demands of the 21st century require a systemic and collaborative perspective to promote the long-term development and success of all children. The purpose of this international comparative study is to investigate students’ mindsets and behaviors for school, college, and career success. The results revealed that there are key factors significantly impact on the students’ perceptions on academic, emotional, and career development. The author hopes this study will add to the limited existent research on educating the whole child. Also, this study should assist in future policies and practices by providing explorative analyses for students’ attitudes or beliefs for achieving their college and career goals.
Keywords: academic success; career readiness; dept.edl; emotional development; peer-reviewed

A systematic approach to exploring college and career readiness program needs within high-poverty urban public schools - Yavuz, Olcay; Parzych, Jennifer; Generali, Margaret (Education and Urban Society, 2019)
This quantitative correlational study was designed to investigate whether the core and enrichment college readiness program needs within high-poverty urban schools significantly varied with respect to grade level and stakeholder perceptions. Statistically significant differences were discovered in parent, student, and faculty perceptions in core and enrichment programs related to high-poverty urban school needs. The findings provide valuable information about how to design student academic and counseling services strategically and effectively to increase college and career readiness for low-income, urban students. Findings also provide effective strategies for school leaders, educators, and counselors regarding urban school college and career readiness program needs so that resources can be intentionally distributed in areas of greatest importance.
Keywords: accountability; change; dept.csp; dept.edl; peer-reviewed; school improvement; school reform; urban education

Applying SERVQUAL: Using service quality perceptions to improve student satisfaction and program image - Gregory, Jess L. (Journal of Applied Research in Higher Education, 2019)
Purpose: Austerity approaches in higher education require choosing the highest leverage strategies of increasing student satisfaction. Attending to student perceptions of program/service quality (SERVQUAL) is a means to identify areas that have the greatest return on investment. The paper aims to discuss these issues. Design/methodology/approach: This study explores how a program has applied the SERVQUAL model and survey to identify areas for growth. Findings: The survey of 57 students in a cohort-based doctoral program demonstrated the smallest gaps (highest satisfaction) with the domains of empathy (1.33) and responsiveness (1.30) and the lowest with reliability (2.03), tangibles (1.97) and assurance (1.90). Practical implications: While not all of the five dimensions are within the purview of a program to address (some may require funding that is determined at a college or university level), many of the gaps can be addressed by adopting procedures and policies that increase transparency so that students can moderate their expectations and faculty and staff can provide reliable information. Additionally, the use of the SERVQUAL model provided this program with specific, actionable information that could be used to improve the program. Originality/value: The study includes a review of studies that have applied the SERVQUAL model in higher education. The application of SERVQUAL to a cohort-based doctoral program to identify program improvements and steward program image fits into a gap in the extant literature. © 2019, Emerald Publishing Limited.
Keywords: Market-driven forces in education; SERVQUAL; Service quality; Student satisfaction; dept.edl; peer-reviewed

Editorial: Educational leadership and social justice - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2019)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Preparing perform and impact ready school leaders for improving urban school success - Yavuz, Olcay; Gülmez, Gülçin (Research in Educational Administration & Leadership, 2018)
In an effort to develop and support high quality urban school leaders, this study examined what factors affect pre-service urban school leaders’ perception of preparedness for performing instructional leadership activities. The findings revealed that participating in a leadership training program is the only significant factor that predicts urban educators’ scores on instructional leadership readiness measures. By examining perception of preparedness of aspiring urban school leaders the findings contribute to our understanding about some perspectives to prepare and develop urban school leaders solve large and complex problems related to the curriculum, instruction and assessment. Implications for preparing performance ready school leaders in high need urban schools are further discussed. © Official Publication of EARDA-Turkish Educational Administration Research and Development Association.
Keywords: Leadership training; Perception of preparedness; Urban leadership; dept.edl; peer-reviewed

School leadership training: Are we preparing future talent managers? - Yavuz, Olcay; Madonia, Peter; Abolafia, Victoria M. (Uluslararası Liderlik Eğitimi Dergisi, 2018)
Effective leadrship talent management practices are important components of successful organizations. This correlational quantitative study is designed to inform educational leadership training programs in their work to revise their curricula and to utilize the candidates’ perception data to ensure successful program delivery and outcomes. Particularly, the findings of this study aim to inform educational leadership preparation practices on developing talent managers who can recruit, hire, retain, and support the most talented and high qualified teachers, as well as support staff available in the education job market. Results indicate that after completing the first year of educational leadership training only around half of the aspiring school leaders felt performance or impact ready to serve as talent managers, in order to select and develop highly qualified educators to increase the success of all students. The findings also suggest the importance of understanding how various factors predict an individual’s perception of preparedness to perform talent management leadership activities. Therefore, the study results may serve to enrich conversations of educational leadership training programs, guide program evaluation efforts, and help ensure candidates in educational leadership programs are exposed to talent management and strategies in their coursework. This may help future school leaders clearly and purposefully apply their knowledge and skills.
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Perceptions of social emotional learning needs in high poverty schools - Generali, Margaret M.; Yavuz, Olcay; Parzych, Jennifer (Journal of Contemporary Administrative Science, 2018)
This paper explores the perceived social emotional learning needs of students in high poverty schools. Social emotional learning (SEL)is recognized within the literature as critical to success in school and in life. Emergingwork supports the acquisition of a SEL skillset within grades kindergarten through twelve ( K-12) schools. This survey examines the perceptions of social emotional needs as reported by students, parents and school faculty members across four different high poverty schools in the USA. Findings provide effective strategies and valuable data for school leaders, educators, and counselors in addressing the social emotional needs of urban students.
Keywords: dept.csp; dept.edl; peer-reviewed; ⛔ No DOI found

Urban tween talk about using mobile phones for learning - Arafeh, Sousan; Kuszpa, M; Weller, M; Mitchell, T (Mobile Learning: Perspectives on Practice and Policy, 2018)
There can be no doubt that mobile technologies are here to stay. Global mobile traffic grew 74 percent in 2015 alone, with 563 million devices and connections added -- most of them tablets and Smartphones. This growth has been 4000-fold in the past 10 years and 400 million-fold in the past 15 years (Cisco, 2016). Mobile technologies permeate the lives of 21st century citizens as mainstays of organizational and institutional day-to-day operations, commerce, and communication and as tools used to support individuals' personal, social, and career responsibilities. In both the corporate and educational worlds, e- and m-learning and marketing with mobile technologies are moving forward at breakneck speed with, in many cases, a blurring of traditional sector boundaries. As neither the technology nor the uses are static, exploring practices and policies that underpin this quickly shifting mobile technology context is crucial for ensuring its intelligent, purposeful, and equitable use. This edited book provides a venue for researchers to share their work on mobile learning with a focus on uses for mobiles in informal settings and PK-20 classrooms, language learning, mobile gaming, leadership and policy issues, and what mobile learning in the future may be. It assists researchers and educators to consider and answer questions such as: What is "mobilelearning" today How can mobiles be used to enable learning How is mobile learning crossing or connecting economic, social, and/or cultural sectors How do specific cultural practices with media influence mobile learning (e.g
Keywords: dept.edl

Access versus success: Services for students with disabilities in postsecondary education. - Sassu, Kari (Journal of Educational Leadership and Policy Studies, 2018)
Keywords: dept.csp; peer-reviewed; ⛔ No DOI found

Attitudinal instrument development: Assessing cognitive, affective, and behavioral domains of teacher attitudes toward teaching all students - Gregory, Jess L; Noto, Lori A (Cogent Education, 2018)
Despite their entree into the physical space of general education classrooms and the expected instruction of the core academic standards, students with disabilities may still be excluded. Successful inclusion requires a commitment at district, school and classroom level. The attitude of the general education teacher toward the inclusion of students with disabilities is a critical component in the success of inclusionary efforts. The attitudes toward teaching all students (ATTAS-mm) instrument are a nine-item scale with strong reliability and validity that measures educator attitudes. The three subscales: believing all students can succeed in general education classrooms (cognitive), developing personal and professional relationships (affective), and creating an accepting environment for all students to learn (behavioral) explain nearly 80% of the variance in scores. The unstandardized Cronbach alpha for the entire ATTAS-mm scale was 0.83. The three subscales also demonstrated acceptable reliability values (Cognitive, 0.72; Affective, 0.93; Behavioral, 0.84). With strong internal reliability and validity established through a panel of experts and alignment with cognitive psychology literature, the ATTAS-mm was determined to be a valid and reliable instrument for measuring the attitudes toward teaching all students. © 2018 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.
Keywords: ATTAS-mm; dept.edl; inclusion; instrument development; peer-reviewed; special education; teacher attitudes

Culturally responsive practice and the role of school administrators - Minkos, Marlena L.; Sassu, Kari A.; Gregory, Jess L.; Patwa, Shamim S.; Theodore, Lea A.; Femc-Bagwell, Michele (Psychology in the Schools, 2017)
In recent years, student populations within public schools in the United States have become increasingly diverse, both culturally and linguistically, and are projected to continue to grow in diversity in the future. Consequently, educators must be prepared to support the needs and education of students with multicultural backgrounds who may differ from them. School administrators play an important role in creating safe, accepting school environments and guiding the education of diverse student populations. However, there is a need for additional guidance for school leaders in cultivating schools that promote equity for all students. Using the National Policy Board for Educational Administration (NPBEA) Professional Standards for Educational Leaders as a guiding framework, this paper provides practical suggestions regarding culturally responsive strategies and practices that school administrators might employ in leading diverse school communities.
Keywords: culturally responsive practice; dept.csp; dept.edl; diversity; educational leadership; peer-reviewed

Trust relationships in schools: supporting or subverting implementation of school-wide initiatives - Gregory, Jess L. (School Leadership & Management, 2017)
This article explores trust relationships in schools that involve disparities in power. Trust is a key factor in developing a positive school culture and strong leadership in schools. Even with the flattening of hierarchies through more distributive models of leadership, disparities in power exist and they influence the trust relationships in schools. Through both French and Raven’s and Follett’s conceptualisations of power, five brief autobiographical stories about trust in schools are deconstructed. Lessons for leadership are gleaned from the power relationships in the autobiographical stories of trust shared by public school educators. In addition, general recommendations are offered that are relevant for all levels of school leadership including but not limited to the instructional coach, the curriculum supervisor, the building principal, and the classroom teacher.
Keywords: Follett; French & Raven; Trust; change leadership; dept.edl; educational leadership; power

Improving student achievement through strengthening principal and school counselor partnership - Yavuz, Olcay; Cayirdag, Nur; Dahir, Carol; Gümüşeli, Ali İlker (International Journal of Educational Reform, 2017)
Keywords: dept.edl; peer-reviewed

School principal perceptions of the school counsellor's role: Traditional or transformed? - Yavuz, Olcay; Dahir, Carol; Gumuseli, Ali Ilker (Journal of Educational Leadership, Policy and Practice, 2017)
There is a continued emphasis on the importance of building collaborative working relationships between school principals and counsellors to address the growing academic, career and college readiness, and social-emotional needs of students in K-12 schools. This study explored and analysed 1466 school principals' perceptions around important school counselling priorities, perceptions, and activities that are carried out in Turkish public and private schools. The study additionally explored school principals' expectations of school counsellors' roles and responsibilities as aligned with traditional and transformed school counselling programmes and practices. This study may be of value to school leaders, policy makers and educators interested in revising and improving their school counselling services to meet the complex academic and counselling needs of students in contemporary schools.
Keywords: dept.edl; ⛔ No DOI found

Attitudes of Croatian and Polish elementary school teachers towards inclusive education of children with disabilities - Cwirynkalo, Katarzyna; Kisovarivanda, Tamara; Gregory, Jess L; Żyta, Agnieszka; Arciszewska, Aleksandra; Zrilic, Smiljana (Hrvatska Revija za Rehabilitacijska Istraživanja, 2017)
Inclusive education has been gaining increasing attention from governments throughout the world. Croatia and Poland, two European Union members that ratified the Convention on the Rights of Persons with Disabilities, have been working on issues related to improving the quality of education of children with special educational needs. The aim of this article was to explore the attitudes of Croatian and Polish elementary education teachers towards inclusion of these children in regular classes. The sample consisted of 98 elementary education teachers from Croatia (N=50) and Poland (N=48). A diagnostic survey based on the Teacher Attitudes Toward Inclusion Scale (TATIS) (Cullen, Gregory, & Noto, 2010) was used. The instrument allows measurement of three main components of attitudes: teacher perceptions of students with mild to moderate disabilities (POS), their beliefs about the efficacy of inclusion (BEI), perceptions of professional roles and functions (PRF), as well as their general attitudes towards inclusion. We found that Polish teachers received significantly higher scores on two subscales: POS and BEI. We also found that age and place of living influenced the attitudes of teachers in the two groups. Implications for practice are discussed. © 2017, University of Zagreb, Faculty of Political Sciences. All rights reserved.
Keywords: Children with disabilities; Inclusive education; Teachers’ attitudes; dept.edl; ⛔ No DOI found

Mindfulness as a prerequisite to effective leadership; exploring the constructs that foster productive use of feedback for professional learning - Day, Danette V; Gregory, Jess L (Interchange, 2017)
This paper proposes a model that integrates mindfulness, ego, and mindset as filters of the information available for professional learning. The paper explores connections between mindset, ego, and mindfulness that promote or inhibit an educator’s ability to use feedback for learning. A leader’s commitment to creating spaces for meaningful use of all types of feedback promotes a school climate that encourages risk taking in learning. Mindfulness, the cultivation of the ability to pay attention to the present moment non-judgmentally, is a prerequisite skill to the effective delivery and use of feedback to promote professional learning. The development of mindfulness requires practice of a method and the continual application of mindfulness to remain open to learning from feedback. © 2017, Springer Science+Business Media B.V.
Keywords: Effective leadership; Ego; Feedback; Mindfulness; Mindset; Professional learning; dept.edl

Instructional scaffolding to promote an autonomous learner - Gregory, Jess L (Preparing Pre-Service Teachers for the Inclusive Classroom, 2017)
An autonomous learner has developed an intrinsic motivation that drives him or her to pursue learning for the inherent satisfaction and enjoyment that stems from the acquisition of knowledge. This chapter presents strategies for teachers to develop a classroom of more autonomous learners. In addition to some strategies and sequencing of activities to maximize their impact, the chapter presents Universal Design for Learning as a framework for thinking about all teaching and ways to apply differentiated instruction to meet the needs of all learners. While there is a focus on the experience of a novice teacher, the content of this chapter is relevant for all educators looking to reinvigorate their practice to empower students to be more in command of their own learning.
Keywords: dept.edl